GAMBARAN HASIL PEMERIKSAAN SITOLOGI PENDERITA KANKER SERVIKS PASCA TERAPI RADIASI BERDASARKAN KELOMPOK UMUR DI INSTALASI RADIOTERAPI RSUD ARIFIN ACHMAD PERIODE TAHUN 2009–2013 - Herman, Awanda; Sofian, Amru; Chandra, Fifia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Radiation therapy is a therapeutic option for cervical cancer, and expected to have optimal outcomes, The results of radiation therapy is different for each patient depending on the sensitivity of cancer cells to radiation that is influenced by age, it can be reviewed by looking at the cell's response to radiation based on the presence or absence of malignant cells that found in the results of cytologic examination after radiation therapy. This research aimed to describe the results of cytological examination of cervical cancer patients after radiation therapy by age group in Radiotherapy Installation Arifin Achmad general hospital of Riau Province Period 2009-2013. The type of this research was descriptive retrospective with population are medical recodrs of cervical cancer patients who had undergone radiation therapy in the form of 25 full time external radiation therapy without chemotherapy in Radiotherapy Installation Arifin Achmad General Hospital of Riau period 2009 to 2013. The sample is the medical record that eligible as population that is as much as 78 medical records. The result of this research was found the largest age group who performed radiation therapy was 40-49 years old (41%), while the largest age group who have a cytological examination found no malignant cells most is 40-49 years old (12.8%), the age group that has the results malignant cells are found in the form of the age group 40-49 years old and 50-59 years old with patients respectively (1.3%) and the largest age group who do not have the data post-radiation cytology result is 40-49 years old (26 , 9%). The largest age group who have a cytological examination found no malignant cells most is people who do a cytological examination more than once that is age group > 60 years old (55.6%) and resulted in the malignant cells are found in the age group 50-59 years old (11 , 1%). Key words: cervical cancer, cervical cancer radiation, cytology results based on age